P.Oxy. VIII.1079 (P18) Closing on a 'Curious' Codex? - Malik, Peter (New Testament studies, 2019)
Codex was by far the most widely attested book form among early Christian literary papyri. Nevertheless, the papyrological record does include several notable exceptions, two of which contain parts of the book of Revelation (18 and 98). Recently, the former's status as a roll has been disputed by Brent Nongbri, who suggested that, instead, 18 is more likely to be a miscellaneous codex. This article provides a fresh look at the extant evidence and critically reviews Nongbri's case. In closing, brief reflections on the manuscript's social setting are offered.